2024
DOI: 10.1021/acs.est.4c00204
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Electronic Structures of Pt on Pt/TiO2 Catalyst for Boosting Toluene Oxidation

Qian Zhao,
Yan Zhang,
Guangzhi He
et al.

Abstract: Surface hydroxyl groups commonly exist on the catalyst and present a significant role in the catalytic reaction. Considering the lack of systematical researches on the effect of the surface hydroxyl group on reactant molecule activation, the PtO x /TiO 2 and PtO x−y (OH) y /TiO 2 catalysts were constructed and studied for a comprehensive understanding of the roles of the surface hydroxyl group in the oxidation of volatiles organic compounds. The PtO x /TiO 2 formed by a simple treatment with nitric acid presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In recent years, the catalytic materials of metal nanoparticles loaded on ceria surface have attracted wide attention, which show excellent performances for efficient oxidation of VOCs. As a typical active support, the ceria support could take part in the reaction directly and accelerate oxygen circulation; moreover, a strong interaction between the noble metal and the ceria support might occur on the surface, bringing about charge transfer and atom migration. As a result, the electronic and structural properties of catalysts would be changed significantly, deeply influencing the catalytic activity, selectivity, and stability. Lu et al found that tunable partial negative charges on Pt were achieved by suppressing roughening of the support surface, favoring O 2 spillover from TiO 2 to Pt . Zhang et al suggested that the Pt particle size would affect the chemical valence of Pt and adjust the strong metal–support interaction .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the catalytic materials of metal nanoparticles loaded on ceria surface have attracted wide attention, which show excellent performances for efficient oxidation of VOCs. As a typical active support, the ceria support could take part in the reaction directly and accelerate oxygen circulation; moreover, a strong interaction between the noble metal and the ceria support might occur on the surface, bringing about charge transfer and atom migration. As a result, the electronic and structural properties of catalysts would be changed significantly, deeply influencing the catalytic activity, selectivity, and stability. Lu et al found that tunable partial negative charges on Pt were achieved by suppressing roughening of the support surface, favoring O 2 spillover from TiO 2 to Pt . Zhang et al suggested that the Pt particle size would affect the chemical valence of Pt and adjust the strong metal–support interaction .…”
Section: Introductionmentioning
confidence: 99%